2007
DOI: 10.17221/682-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Thermal inactivation of Enterococcus faecium

Abstract: AbstractŠpelina V., Schlemmerová L., Landfeld A., Kýhos K., Měřička P., Houška M. (2007): Thermal inactivation of Enterococcus faecium. Czech J. Food Sci., 25: 283-290.Data for thermal inactivation of working suspension of Enterococcus faecium in model solutions were acquired and used to develop a mathematical model for thermal inactivation of the bacterium. The model is valid within the water activity range 0.97 to 0.99; pH range 6.0 to 7.6; temperature range 60°C to 65°C, and was determined for the microorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Previous study suggested that the temperature range from 55°C to 65°C is critical for effective elimination of enteric/pathogenic bacteria components. Thermal inactivation of working suspension of Enterococcus faecium was performed between temperature ranges 60°C to 65°C that supports current study [24].…”
Section: Resultssupporting
confidence: 84%
“…Previous study suggested that the temperature range from 55°C to 65°C is critical for effective elimination of enteric/pathogenic bacteria components. Thermal inactivation of working suspension of Enterococcus faecium was performed between temperature ranges 60°C to 65°C that supports current study [24].…”
Section: Resultssupporting
confidence: 84%
“…go behind by E. faecium. The presence of the bacteria E. faecium in processed milk is explained by often capable of these microorganisms survives during pasteurization process (18).…”
mentioning
confidence: 99%
“…It is estimated that 30% of enterococcal infections in hospitals are caused by vancomycin-resistant strains [ 3 ]. These bacteria can survive mild pasteurization at a temperature of 62.5°C for 20 minutes [ 6 ]. E .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of enterococci in food is the result of contamination caused by low hygiene levels [ 6 , 11 ]. Fish and seafood can be habitats for enterococci originating from rivers, lakes, and seawater, which are often contaminated with municipal sewage and aquaculture effluents [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation